The measurement of successfully completed projects funded by the European Union - Siposné Sinóros-Szabó, Laura (Acta Agraria Debreceniensis, 2015)
Projects funded by the European Union contribute significantly to the socio-economic development of Hungary, its increasing competitiveness, thereby the local people's general level of satisfaction, their ”happiness and prosperity”. Successful spending from the Union's funds, successful project implementation directly impacts all actors in the Hungarian economy and society. Therefore, to examine the factors that support or jeopardize the implementation of the projects is a priority at EU and national levels. My research and doctoral dissertation aims to develop a methodology to assess the management efficiency of projects supported by the European Union, implemented in Hungary taking into account all measurable factors (technical and special expertise) and the "suspected" factor (EU thinking learning).I intend to draw up guidelines for future EU funded project management teams to realize projects successfully for the benefit of Hungary.